Coincidence of Guillain-Barré syndrome presenting with Landry’s acute flaccid paralysis and transverse myelitis - Kalinova, Desislava (Reumatologia, 2019)
Transverse myelitis is one of the causes of acute transverse myelopathy; three main categories are described in the differential diagnosis of transverse myelitis: demyelination (multiple sclerosis, neuromyelitis optica), infections (herpes zoster and herpes simplex virus), and some autoimmune connective tissue disorders (systemic lupus erythematosus, vasculitis). The authors present a clinical case of a 33-year-old patient with transverse myelitis occurring in the course of acute inflammatory demyelinating polyradiculoneuropathy (Guillain-Barré syndrome). The patient’s medical history was notable. The patient was diagnosed with thrombotic thrombocytopenic purpura (Moschcowitz syndrome) and leukocytoclastic vasculitis when he was 12 years old.